Comportamiento agronómico y valor nutricional del pasto saboya (Panicum maximun) con abonos orgánicos sólidos en época lluviosa - Zambrano Anchundia, Oder Angel (2012)
This research work was carried out on the farm "San Carlos", located at Km 28 via Quevedo - Santo Domingo, whose geographical coordinates are as follows: 79 ° 29 'west longitude and 0 ° 52' south latitude at an altitude of 120 meters. The investigation lasted 90 days. The management of the trial was conducted according to the specifications established for the management of grass Savoy. Raised the overall objective: To evaluate the behavior and nutritional value of grass Savoy (Panicum maximum) with solid manure during the rainy season and specific: a) Determine the best level of manure in the agronomic performance of grass Savoy b) Establish the benefit cost of the treatments under study. Subject to the assumptions: a) The level of 1500 kg ha-1presented the best agronomic b) With the level of 1500 kg ha-1we get the best benefit - cost. The experimental design was randomized complete block (RCBD) with four treatments and four repetitions. To determine the difference between treatment means was used multiple range test of Tukey at 5% probability. Application of T4 (1500 kg ha-1 solid organic manure AGROPESA, induced a higher yield of biomass feedstocks, number of leaves, fresh weight of stem, leaf and plant, as well as a greater length of leaf, compared with control (without fertilizer T1) at 30, 45 and 60 days. The dry matter yield achieved at 60 days was higher in the T4 treatment, with a production of 7041 kg DM ha-1, where the effect of organic fertilizer use efficiency. We observed that dry matter yield increases with the age of the grass in all treatments, being higher at 60 days. Plant height in all treatments was higher than two meters in height, but not statistically differ. However we observed a greater increase in plant height dosed with organic fertilizer (1500 kg kg ha-1). The application of organic fertilizers, did not influence the composition bromatological treatments, however the older the grass if they showed increases in dry matter and fiber, and a decrease in protein content.